The Compatibility of “Guess What” Textbook Based on English Final Exam Framework 2018/2019 - Andyna Rakhma Ilahi (STKIP PGRI SIDOARJO, 2019)
This study is used descriptive qualitative because the researcher wants to understand the contexts. The researcher is focused on the analysis of “Guess What” textbook. There are 2 parts of this book; pupils’ book and activity book. The students in this school only use the activity book to do the exercise while the teacher has both. In this study, the researcher took the data from the materials in the textbook to analyze whether this book compatible with the question indicators in English final exam framework or not. The result of this study tells that the compatibility is 62% and the incompatibility is 38% from the total questions 50 numbers, 30 numbers are multiple choice, 15 numbers are short answer and 5 essay questions. It can be concluded that this textbook is compatible with question indicators in English final exam framework 2018/2019.